Formation of Nucleophilic Allylboranes from Molecular Hydrogen and Allenes Catalyzed by a Pyridonate Borane that Displays Frustrated Lewis Pair Reactivity. Issue 52 (22nd October 2020) - Hasenbeck, Max; Ahles, Sebastian; Averdunk, Arthur; Becker, Jonathan; Gellrich, Urs
Abstract: Here we report the in situ generation of nucleophilic allylboranes from H2 and allenes mediated by a pyridonate borane that displays frustrated‐Lewis‐pair reactivity. Experimental and computational mechanistic investigations reveal that upon H2 activation, the covalently bound pyridonate substituent becomes a datively bound pyridone ligand. Dissociation of the formed pyridone borane complex liberates Piers borane and enables a hydroboration of the allene. The allylboranes generated in this way are reactive towards nitriles. A catalytic protocol for the formation of allylboranes from H2 and allenes and the allylation of nitriles has been devised. This catalytic reaction is a conceptually new way to use molecular H2 in organic synthesis. Abstract : The in situ formation of nucleophilic allylboranes from H2 and allenes is reported. The reaction is catalyzed by pyridonate borane that displays frustrated‐Lewis‐pair reactivity. The allylboranes that are generated in this way are reactive towards nitriles. Mechanistic investigations show that a change in the binding mode of the pyridonate substituent upon hydrogen activation is essential for the formation of the allylboranes.